Archaeological workS by the Taman Expedition of the State Academy for the History of Material Culture - Vinogradov, Yu.A.; Grigorieva, O.V.; Medvedeva, M.V. (Материалы по археологии и истории античного и средневекового Причерноморья, 2022)
The Taman Expedition of the State Academy for the History of Material Culture (SAHMC) was organized in 1930. It was headed by a remarkable archaeologist Alexander A. Miller. The main goal of the expedition should have been a systematic study of ancient sites located on the Taman Peninsula, but the research there lasted only two years. During this time, the archaeological map of the Taman Peninsula was created. The hillfort of Tmutarakan/Germonassa became the main point of the field research. Small-scale excavations were also undertaken at Phanagoria, at the settlement near Suvorov’s Fortress in Phanagoria, and in Patrei. In Patrei, a winery dating back to the Roman times was recovered. The main reason why the expedition lasted for such a short period was that the head officials in the SAHMC ignored the interests of archaeologists in Moscow and did not agree to any compromises. This led to a serious conflict which resulted in the stoppage of the promising research project and political reprisals against some of its participants.